2004
DOI: 10.1088/0967-3334/25/6/005
|View full text |Cite
|
Sign up to set email alerts
|

Pressure pulse velocity is related to the longitudinal elastic properties of the artery

Abstract: It is known that arteries in their natural position are always subject to a longitudinal stress. However, the effect of this strong longitudinal tension has seldom been addressed. In this paper, we point out that the traditional pulse wave velocity formulae considering only the circumferential elasticity fail to include all the important energies. We present a vigorous derivation of a pressure wave equation, the pressure wave equation with total energy, which considers all the important energies of the whole a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Although these can improve the accuracy of the results to some extents, they are often too cumbersome for practical uses. 9 The results obtained from this study show that both the proposed methods can produce relatively correlated PWV estimates.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…Although these can improve the accuracy of the results to some extents, they are often too cumbersome for practical uses. 9 The results obtained from this study show that both the proposed methods can produce relatively correlated PWV estimates.…”
mentioning
confidence: 60%
“…8 Some researchers have tried to take the oscillating wall as a correction factor that results in complex equations and parameters. 9 To avoid the direct use of pulse pressure, others have measured PWV by estimating the time delay between waveforms recorded simultaneously at two positions. 2,8 Characteristic impedance of an arterial segment is directly related to regional arterial PWV, which in turn is correlated to arterial wall stiffness and wall thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Among the rare studies related to prosthesis mechanics available in literature, the investigations of Dobrin (1995) showed that vascular prosthesis are exposed after implantation to longitudinal deformations due to blood flow. Wang et al (2004) demonstrated that the longitudinal elasticity is an important factor in hemodynamics and in the treatment of cardiovascular diseases, because the longitudinal compliance mismatch between the natural artery and the synthetic graft may promote graft-artery intimal hyperplasia by altering suture-line stresses. In a study performed by Irina (2005), the most common cause of failure of vascular prostheses is the formation of intimal hyperplasia at the anastomosis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the study of arterial distensibility has shown to be clinically important in the prognosis of systolic hypertension and cardiovascular morbidity [3]. An indirect method for the assessment of arterial distensibility can be obtained by measuring the pulse wave velocity (PWV), which is related to arterial distensibility by the Moens-Korteweg formula [4,5]. A parameter termed pulse transit time (PTT) which is based on the principle of PWV has demonstrated its potential in paediatrics cardiovascular studies [6,7].…”
Section: Introductionmentioning
confidence: 99%